The Effectiveness of Adiwiyata Programme on Environmental Awareness of SMP Negeri 27 Makassar Students - Try Suyanti; Muh Sri Yusal; Ahmad Hasyim; Herlina Herlina (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2026)
Background:  The Adiwiyata school programme aims to foster a sense of responsibility among the school community regarding environmental protection and management through good school governance. This study aims to examine the effectiveness of the Adiwiyata programme in fostering environmental awareness among students at SMP Negeri 27 Makassar as contribution towards achieving the Sustainable Development Goals. Unlike previous studies, which generally employed a qualitative descriptive approach, this study utilised a quantitative approach to obtain more measurable empirical evidence regarding the causal relationship between the programme and students’ attitudes. Methodology: The research methodology employed a quantitative approach using linear regression analysis and the coefficient of determination test. Sampling was conducted using purposive sampling. Instruments used included questionnaires, observation sheets, and documentation to measure programme implementation and students’ environmentally conscious behaviour. Findings: The study indicate that the implementation of the Adiwiyata programme and students’ environmentally conscious attitudes fall into the ‘very good’ category, carried out in a participatory manner involving the entire school community and relevant partners. The coefficient of determination value of 0.681 indicates that the Adiwiyata programme has a strong influence on students’ environmentally conscious behaviour, whilst 31.9% is influenced by other factors outside scope of this study. Contributions: This study serve as a source of literature and measurable empirical evidence regarding the impact of the Adiwiyata programme on students’ environmental awareness, integrating cognitive, affective and behavioural dimensions. In practical terms, this study can serve as a reference for other schools wishing to implement similar programmes